Analysis to assess menstrual poverty in vulnerable and non-vulnerable populations served in a public service in Brazil - LUCARELLI, ADRIENNE; Ferreira da Silva, Amanda Avila (Journal of Health & Biological Sciences, 2024)
Objective: this study aims to identify the factors influencing menstrual period management among vulnerable and non-vulnerable patients treated at the Emergency Department of a public hospital. Methods: the sample comprised patients who sought care at the Emergency Department of Santa Casa de São Paulo between July 2022 and August 2023. Participants were stratified by gender (women, trans men, or non-binary individuals who menstruate) and social vulnerability (homeless, living in non-permanent housing such as shelters, without fixed income, or earning less than the minimum wage). Inclusion criteria were women, trans men, or non-binary individuals who menstruate, aged 18 years or older, and those who signed the Informed Consent Form (ICF). Exclusion criteria were individuals not menstruating or unable to sign the informed consent. Statistical analysis was performed using the Chi-Square Test. Results: seventy (70) patients participated in this study, 34 of whom were classified as vulnerable and 36 as non-vulnerable. Key differences between the groups included hygiene practices during menstruation, frequency and ability to purchase menstrual products and medications, type of material used, duration of exposure to the material, and health conditions during menstruation. Similarities between the groups were observed in the most commonly used materials, contraceptive methods, menstrual flow volume, and experiences of embarrassment. Conclusion: the study reveals both differences and similarities between the groups. Understanding these factors allows for the proper management of the menstrual period in vulnerable patients, supporting the development of public policies aimed at improving gynecological health outcomes for these populations.